Penerapan Media Papan Musi untuk Meningkatkan Hasil Belajar Matematika pada Materi KPK dan FPB di Kelas IV SD Negeri 064966 Medan - Siregar, Lisa Febriyanti; Sari, Suci Perwita; Pakpahan, Mariani Rosmida (ALSYS, 2025)
Mathematics is often perceived as difficult and boring by elementary school students, particularly regarding the topics of Least Common Multiple (LCM) and Greatest Common Factor (GCF), which results in low learning outcomes due to limited conceptual understanding and a lack of engaging, contextual learning media. This study aims to examine the improvement in students’ mathematics learning outcomes through the application of the MUSI (Multifunction) board media, an educational game-based tool designed to help students concretely and enjoyably grasp the concepts of LCM and GCF. The research employed Classroom Action Research (CAR) conducted over two cycles, involving 20 fourth-grade students at SD Negeri 064966 Medan during the even semester of the 2024/2025 academic year. Each cycle comprised planning, implementation, observation, and reflection stages, using observation sheets and learning outcome tests as instruments. The results revealed an increase in learning mastery from 74.3% in cycle I to 92.5% in cycle II. Additionally, student activity improved from a “fair” to an “excellent” category. These findings demonstrate that the MUSI board media is effective in enhancing students’ mathematics learning outcomes and actively engaging students in the learning process.